Fuzzy logic to adjust room temperature depending on the number of people - Muhammad Furqon Siregar; Chairul Imam (Institute of Computer Science (IOCS), 2023)
This study focuses on discussing how fuzzy logic can be used in temperature control systems. To avoid unsuitable and excessive performance as a result of the growing number of individuals entering the room, fuzzy logic is utilized to determine the amount of values provided. The effectiveness of the system in controlling the temperature and the quantity of individuals entering the space is its performance. When people enter the space, the sensor system counts them to establish the room's capacity. The ATmega328 microcontroller was used in the creation of this system. The quantity of people entering the room is forecast using PIR and ultrasonic sensors. To prevent system failure, the maximum number is restricted to 250 persons for calculating and evaluating system performance. In this case, the Tsukamoto fuzzy logic model was applied, with experimental results showing increased accuracy in determining how many rotations the dynamo and relay experience. The measured average value of the results obtained an accuracy of 54.11%, and the system shows that it is more stable than without applying the fuzzy logic model.